Head Accelerations during a 1-on-1 Rugby Tackling Drill Performed by Experienced Rugby Union Players - Tahere Reha (MDPI AG, 2021)
Rugby Union is a popular sport played by males and females worldwide, from junior to elite levels. The highly physical skill of tackling occurs every few seconds throughout a match and various injuries associated with tackling are relatively common. Of particular interest are head injuries that result in a concussion. Recently, repeated non-injurious head impacts in sport have attracted the attention of researchers interested in brain health. Therefore, this study assessed head movement during repeated rugby tackle drills among experienced Rugby Union players. Experienced male and female participants performed 15 1-on-1 tackles in a motion analysis laboratory to measure the head movements of the ball carrier and tackler during each tackle, using three-dimensional motion capture. The average peak acceleration of the head for ball carriers was 28.9 ± 24.08 g and 36.67 ± 28.91 g for the tacklers. This study found that the type of head impacts common while performing a tackle in Rugby Union are similar to those experienced by soccer players during heading, which has been found to alter brain function that lasts hours after the event. This has important implications for player health and suggests that mitigation strategies should be considered for Rugby Union.